Оптимізація ведення цукрового діабету 2-го типу згідно з принципами консенсусу ADA/EASD - Полозова, Л. Г. (Clinical Endocrinology and Endocrine Surgery, 2010)
The lecture deals with approaches to the choice of therapy in patients with diabetes mellitus type 2, based on the principles of evidence-based medicine. The advantages of diabetes type 2 treatment by a fixed combination of glimepiride and metformin — a drug Amaryl M® was shown for patients which failed to achieve compensation through lifestyle changes and taking of metformin.